Changes in resource use and property rights prompted by the adoption of dairy enterprises - Swallow, K.A. (International Livestock Centre for Africa, 1994)
This study is being undertaken as a Ph.D. dissertation (University of Wisconsin-Madison) in conjunction with the ILCA programme in Mombasa, Kenya. The general objective of the research is to understand how institutions support techniques. This is important to understand because economic development depends not only on increases in productive capacity but also on the development of institutions that support that production. The research is based on a case study of change in cattle feed production techniques, with a focus on access to inputs used in different feed production techniques. Specific questions addressed in the research include: (1) How do the institutions concerning access to feed change and who would find this worthwhile? (2) Which farmers are able to shift, for example, from grazing to the cut & carry system? grazing to the cut & carry system? A combination of qualitative and quantitative research methods is being used and listed in the order that they were used. Preliminary findings & observations are also outlined, and Institutions influencing the use of these feed techniques are discussed. This include grazing, tethering and cut and carry